Preliminary Checklist of M.A. Theses and Ph.D. Dissertations Related to Asian American Studies in the UCLA Library - Lin, Che-Hwei, Comp. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
Three hundred and twenty-five references are compiled in the preliminary checklist. Items are arranged alphabetically by author, and encompass research conducted in various disciplines about Chinese, Japanese, Filipino, Hawaiian, and Korean subgroups. Among the topical areas covered by the research studies are the following: cultural conflicts, demographic and ecological analysis, changing sociocultural patterns, problems of assimilation and cultural pluralism, family structure and extended kinship, cultural and linguistic features involved in cross-cultural communication, school achievement and socioeconomic background, interracial marriages, occupational mobility, social welfare services, marriage and family relationships, community life, and religious issues. (AM)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Asian Americans; Asian Studies; Bibliographies; Chinese Americans; Doctoral Dissertations; Filipino Americans; Japanese Americans; Korean Americans; Masters Theses; Research Projects; Reference Materials, Bibliographies